KONTRIBUSI TASAWUF-PSIKOTERAPI TERHADAP PENDIDIKAN ISLAM - Khairunnas Rajab (Jurnal Pendidikan Islam, 2013)
This paper intends to outline the contribution of psychology of religion psychotherapy that evolved into a religion psychoteraphy with style Islamic (Sufi) on education, especially Islamic education. The approach used in this paper is Philosophical approach that is examining the structure of tasawuf psychotherapy that is further analyzed in the context of Islamic education discourse. The pattern of tasawuf psychoteraphy can be implemented in education, specifically in Islamic education, both substantively, methodically, and didactically. Substantively Islamic education aims to teach, improve, form and fix morals of madzmûmah to be karîmah moral. Methodically, Islam is not only as an educational institution that solely transfers knowledge to the students, but also as a guide, counselor and healer agency for students, parents, teachers and even society itself. Didactically, the relationship between teacher and student is like mursyid and his students. Professional teacher in Sufi‟s understanding is the teacher who has occupied a certain maqâmat as zuhud, wara', taubah, and patient so that he has the maturity and politeness in facing the students.